Avaliação de diferentes sistemas de cultivo in vitro para a micropropagação de Psychotria ipecacuanha (Brot.) Stokes - Batistini, A. P. [UNESP]; Moro, J. R. [UNESP]; França, S. C.; Pereira, A. M S (My University, 2002)
This work was carried out with Psychotria ipecacuanha, a Brazilian medicinal plant the roots of which contain emetine. The main objective was to develop a protocol for the micro-propagation of these species, by testing different culture techniques, the temporary immersion system, and the semi-solid and liquid media systems. In the semi-solid system, experiments were developed in flasks of two different sizes containing MS, B5, and WP media to which were added different growth regulators. Innoculum density was also evaluated. The liquid medium system consisted of MS medium supplemented with different growth regulators. For the temporary immersion system, the MS medium received an addition of 1.5mg/L BAP and 0.5mg/L GA3, and a reverse digital apparatus and vacuum pump were used. The liquid medium system with MS medium supplemented with 1.5mg/L BAP and 0.5mg/L GA3 presented the best results for shoot proliferation in a period of 30 days in culture (2.37 ± 0.32 shoots/explant). Cultures carried out for 90 days in the semi-solid system, using 8.5 × 5.5cm flasks and 3 explants per flask, developed 1.80 ± 0.20 shoots/explant, achieving 3.06 ± 0.51 cm of height adn presented superior survival ratio (96%). Explants cultured in temporary immersion system for 90 days showed 2.30 ± 1.10 shoots/explant achieving a growth of 2.08 ± 0.12 cm and 52% survival.
Evaluation of different systems of in vitro culture for propagation of Psychotria ipecacuanha (Brot.) Stokes
Keywords: Alkaloids; Ipecac; Ipecacuanha; Medicinal plants; Rubiaceae; Tissue culture; emetine; Brazil; culture medium; culture technique; density; growth regulation; liquid culture; medicinal plant; micropropagation; plant growth; plant tissue culture; psychotria ipecacuanha; Cephaelis ipecacuanha; Psychotria ipecacuanha